Capturing protein communities by structural proteomics in a thermophilic eukaryote. Issue 7 (25th July 2017) - Kastritis, Panagiotis L; O'Reilly, Francis J; Bock, Thomas; Li, Yuanyue; Rogon, Matt Z; Buczak, Katarzyna; Romanov, Natalie; Betts, Matthew J; Bui, Khanh Huy; Hagen, Wim J; Hennrich, Marco L; Mackmull, Marie‐Therese; et al.
Abstract: The arrangement of proteins into complexes is a key organizational principle for many cellular functions. Although the topology of many complexes has been systematically analyzed in isolation, their molecular sociology in situ remains elusive. Here, we show that crude cellular extracts of a eukaryotic thermophile, Chaetomium thermophilum, retain basic principles of cellular organization. Using a structural proteomics approach, we simultaneously characterized the abundance, interactions, and structure of a third of the C. thermophilum proteome within these extracts. We identified 27 distinct protein communities that include 108 interconnected complexes, which dynamically associate with each other and functionally benefit from being in close proximity in the cell. Furthermore, we investigated the structure of fatty acid synthase within these extracts by cryoEM and this revealed multiple, flexible states of the enzyme in adaptation to its association with other complexes, thus exemplifying the need for in situ studies. As the components of the captured protein communities are known—at both the protein and complex levels—this study constitutes another step forward toward a molecular understanding of subcellular organization. Synopsis: An integrative structural systems biology approach is presented to systematically characterize native protein communities of dynamically associated protein complexes. Cryo‐electron microscopy detects a metabolon involved in fatty acid synthesis at unprecedented molecular details. In addition to the grouping of proteins into complexes, intracellular function requires a further layer of organization that involves multiple spatially and temporally interacting macromolecular complexes or protein communities. However, experimental approaches to capture this higher‐order proteome organization are still missing. Here, we show that crude cellular fractions from a thermophilic eukaryote retain basic principles of proteome organization, and can be exploited to capture protein communities through integrative structural biology approaches. We report a compendium of 27 protein communities and have experimentally characterized and structurally analyzed one of these comprising enzymes involved in fatty acid metabolism. From the crude extracts, we obtained a cryo‐EM structure of fungal fatty acid synthase that reveals a thus far uncharacterized catalytic intermediate. We demonstrate the feasibility of high‐resolution cryoEM without the need to obtain biochemically highly homogenous samples. Abstract : An integrative structural systems biology approach is presented to systematically characterize native protein communities of dynamically associated protein complexes. Cryo‐electron microscopy detects a metabolon involved in fatty acid synthesis at unprecedented molecular details.